Colegios profesionales, relaciones colegiales y potestad sancionadora - Sanz Rubiales, Iñigo (Revista de Derecho, 2019)
Regardless of doctrinal discussions about Peruvian ordainment, it is undoubtedly deduced that Professional Schools and public Administrations. The juridical relationship between collegiate and School is regarded, in Spanish jurisprudence, as “special subjection relationship”, typically “domestic”, category used traditionally to justify limitation of rights; however, the Peruvian constitutional Court does not assume this doctrine. This work demonstrates that the licit flexibility of the principle of legality derives from the corporate-representative constitution of schools. Consequently, collegiate sanctions cannot be identified with disciplinary sanctions of the personnel. After certain doubts, the Constitutional court states with good criteria the compatibility of both, derived from the diversity of juridical goods protected.